Cognitive Frailty: An Update - Facal, David; Burgo, Clara; Spuch, Carlos; Gaspar, Pedro; Campos-Magdaleno, María (Frontiers in Psychology, 2021)
This review article provides an update of the empirical research on cognitive fragility conducted in the last four years. The studies retrieved were classified in four different categories. The first category includes articles relating cognitive frailty to cognitive reserve and which continue to highlight the importance of educational level. The second category includes recent research on cognitive fragility biomarkers, involving neuroimaging, metabolism and, in a novel way, microbiota. The third category includes research on how cognitive frailty is related to motor development and physical functioning, exploring e.g. the use of technology to study motor markers of cognitive frailty. Finally, in the fourth category, research clarifying the difference between reversible frailty and potentially reversible cognitive frailty has led to new interventions aimed at reducing cognitive frailty and preventing negative health outcomes. Interventions based on physical activity and multicomponent interventions are particularly emphasised. In addition, recent research explores the long-term effects of dual interventions in older adults living in nursing homes. In summary, research on cognitive frailty has increased in recent years, and applied aspects have gained importance.